Associations Between Musculoskeletal Pain Experience and Pressure and Cold Pain Sensitivity: A Community-based Cross-sectional Study of Young Adults in the Raine Study. Issue 1 (January 2019) - Waller, Robert; Smith, Anne J.; O'Sullivan, Peter B.; Slater, Helen; Sterling, Michele; Straker, Leon M.
Abstract : Objectives: To investigate the cross-sectional associations between musculoskeletal pain experience and measures of pressure and cold pain sensitivity in young adults from the Western Australian Pregnancy Cohort (Raine) Study. Participants and Methods: In total, 917 participants were eligible for analysis if they provided data pertaining to musculoskeletal pain status at the 22-year follow-up and had data for at least 1 valid pain sensitivity test. Standardized protocols were used to assess pressure pain threshold (4 sites: lumbar spine, tibialis anterior, upper trapezius, and wrist) and cold pain threshold (wrist). Four pain experience groups ("No pain" [n=562, 61.3%], "Low" [n=84, 9.2%], "Medium" [n=147, 16.0%], "High" [n=124, 13.5%]) were determined by latent class analysis using parameters of pain chronicity, frequency, intensity, and number of pain areas. Variables considered as confounders included sex, age, ethnicity, waist-hip ratio, psychological symptoms, sleep quality, physical activity, sedentary behavior, smoking, and income. Results: There were no associations between pain experience and pressure pain sensitivity after adjusting for confounders. The "Medium" and "High" pain experience groups demonstrated heightened cold pain sensitivity compared with the "No pain" group ( P =0.023), adjusted for sex and smoking. Discussion: This study provides the most extensive investigation of the relationship between musculoskeletal pain experience and pressure and cold pain sensitivity in young adults. Heightened cold pain sensitivity in those classified as "Medium" and "High" pain experience may suggest altered nociceptive processing and has implications for clinical management.